Pengaruh Return On Asset dan Return On Equtiy Terhadap Harga Saham PT Gudang Garam Tbk - Andi Nurwana; Adelia Putri Pratiwi; Andi Jamaluddin (Yayasan Pengembangan Sumber Daya Insani Lamaddukelleng, 2025)
This study aims to analyze the effect of Return on Assets (ROA) and Return on Equity (ROE) on the stock price of PT Gudang Garam Tbk for the 2020–2024 period. This study employed a quantitative descriptive approach with a causal associative design, utilizing secondary data in the form of annual financial reports published by the Indonesia Stock Exchange. Data analysis was performed using multiple linear regression using SPSS version 25 to test the partial and simultaneous effects between variables. The results showed that ROA and ROE had a positive but insignificant effect on stock price, with significance values ​​of 0.792 and 0.859, respectively, and a coefficient of determination (R²) of 0.648. This means that 64.8% of stock price variation can be explained by ROA and ROE, while the remainder is influenced by factors outside the model. Therefore, PT Gudang Garam Tbk's stock price fluctuations are largely influenced by external factors such as government policies, macroeconomic conditions, and market sentiment. Therefore, the company needs to improve the efficiency of asset and equity management to strengthen profitability and provide a positive signal to investors